Relational coupling of multiple streams: The case of COVID‐19 infections in German abattoirs. - Möck, Malte; Vogeler, Colette S.; Bandelow, Nils C.; Hornung, Johanna (Policy Studies Journal, 2023)
After a series of COVID‐19 outbreaks among employees in the German meat‐processing industry, the Work Safety Control Act protecting these workers made it on the government's agenda in July 2020. From a Multiple Streams perspective, local corona hotspots may be understood as policy windows for introducing respective measures. However, this alone is not sufficient to explain agenda setting. This study investigates the coupling of streams within policy windows. Introducing the notion of relational coupling to the MSF research agenda, discourse network analysis provides a new methodology to reveal entrepreneurial activities. Studying the German mass media discourse on the issue identifies two stages: (1) An initial problem brokerage without coupling of core policies, followed by (2) a coupling across all streams based on a focusing event. We argue that relational coupling allows for an enhanced understanding of agenda setting.